Early Laparotomy: A Necessity for Postoperative Intraperitoneal Hemorrhage - Rawal, Suniti; Paudyal, Pooja (Journal of Institute of Medicine Nepal, 2019)
Introduction: Haemorrhage is considered the dreaded complications following any surgery. “Relaparotomy” is a better described terminology for a repeat case postoperative haemorrhage in gynecological surgeries. With increased awareness and early detection and subsequent rise in gynaecological operations have led additional incidence of relaparotomies and further in morbidity and mortality. Methods: The study was conducted from April 2006 - March 2017 including cases of re/laparotomy for intraperitoneal bleeding at TUTH, Nepal. Results: There were 27 cases of intraperitoneal hemorrhage majorly from 20 abdominal surgeries comprising 12(44.4%) abdominal hysterectomies, 6 (22.2%) laparotomy, 1(3.7%) each of diagnostic laparoscopy and abdomino perineal approach and 7(26%) vaginal hysterectomies. Features of hypovolaemic shock in 14(51.8%), marked abdominal distention in 9(33.3%) and blood loss of 400 to 3000 ml was observed. Five (18.5%) cases of active bleeding from pedicales were secured. Oozing from various sites (10, 37%) cured with haemostatic sutures. Generalised oozing post diagonistic laproroscopy, subtotal hysterectomy was done (1, 3.7%). In 2 (7.4%) cases bleeding from fallopian tube and mesosapinx were sutured. Six (22.2%) hematomas were evacuated and bleeders secured. Dissection of left uterosacrial ligament and tearing of infundibulopelvic ligaments (1, 3.7%) were reinforced and sutured. Sputter in the vault (1, 3.7%) were ligated and isolated rise in PT (1, 3.7%) with FFP transfusion. Two succumbed to death, one following diagnostic laparoscopy from adult respiratory distress syndrome and next from VH with PFR anesthetic complications. Conclusion: Proper closure of surgical incision with the right technique, appropriate ligature, careful tying of the blood vessel, monitoring pulse rate and blood pressure in postoperative cases can minimize the morbidity and mortality.